National Ecological Values And Their Development - D.Nazarova (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article covers the essence of national ecological values, their historical and cultural sources and significance in modern society. In the course of the research, the ways of developing ecological values ​​based on national traditions, folk oral literature, religious and spiritual heritage, and scientific and pedagogical approaches were analyzed. In addition, the effective aspects of integrating national ecological values ​​in the educational process, strengthening ecological education through the family and neighborhood institute, organizing practical ecological activities, and using digital technologies were substantiated.